Hijrah Riba dalam Perspektif Dakwah Kontemporer - Ahmad Yusuf Prasetiawan; Muhamad Baedowi (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2023)
Hijrah usury is becoming a trend among urban Muslims. Da'wah is an invitation to goodness and hijrah means transformation or reform in goodness. Hijrah usury is based on normative religious arguments, it should also lead to goodness, both for the perpetrators and for others. The financial industry has dominated the business sector. In Islamic teachings, usury is haram, but not all scholars agree that every bank interest must be usury. This research aims to explore the relationship between the phenomenon of hijrah from usury and contemporary da'wah. This research focuses on the hijrah community in the city of Purwokerto, including: the Riba-Free Society (MTR), the Riba-Free Camp (CBR), and the Kekar ​​Foundation (Anti-Riba Economic Community) Purwokerto. The method used is in-depth interviews with community actors. One of the things to be explored is the argument and experience in using bank credit funds to run a business. The results found that usury hijrah was mostly based on the frustration of business failure. But relevant to the spirit of being better, it encourages the perpetrators to become more religious, live simply and have high solidarity.